Insight into Larvae Settlement and Anti-fouling characteristics of Marine Larvae: Next-generation Sequencing Approach - Chandramouli Kondethimmanahalli (Cutting Edge Research in Biology Vol. 4, 2023)
The academic and industrial marine research is focused on understanding larval settlement and metamorphosis process and hoping to prevent settlement and accumulation of undesirable marine species on underwater structures. The process of settlement at molecular level is largely unknown due to limited genome information available for these species. In recent years, rapid technological advancement in next-generation sequencing (NGS) have opened up the possibilities to sequence genome of marine invertebrate fouling organisms. Barnacle Balanus amphitrite, polychaete Pseudopolydora vexillosa, and Bryozon Bugula neritina transcriptome sequencing using Illumina sequencers accelerated the molecular genomics studies. The genome datasets presented several genes play a crucial role during larval settlement which may aide in the design and development of novel anti-fouling agents.